2017
DOI: 10.1302/0301-620x.99b1.bjj-2016-0295.r1
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative α-defensin test (Synovasure) for the diagnosis of periprosthetic infection in revision total joint arthroplasty

Abstract: With its ease of use and rapid results after approximately ten minutes, Synovasure may be a useful adjunct in the diagnosis of PJI. Cite this article: Bone Joint J 2017;99-B:66-72.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
67
6
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(81 citation statements)
references
References 29 publications
6
67
6
2
Order By: Relevance
“…Gehrke et al, 21 Suda et al, 38 Sigmund et al, 26 and Kasparek et al 25 reported a sensitivity of the lateral flow assay of 92.1, 81.2, 76.5, and 75%, respectively, which is similar to our findings of 73.7% sensitivity. Our study showed that the test had a higher specificity of 92.2%, which is similar to the results shown by Suda et al, 85%, 38 Sigmund et al, 94.7%, 26 and Kasparek et al, 93.3%. 25 Only Gehrke et al reported a specificity of 100%, 21 which has not been replicated by other studies utilizing either the a-defensin laboratory-based immunoassay or lateral flow test.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Gehrke et al, 21 Suda et al, 38 Sigmund et al, 26 and Kasparek et al 25 reported a sensitivity of the lateral flow assay of 92.1, 81.2, 76.5, and 75%, respectively, which is similar to our findings of 73.7% sensitivity. Our study showed that the test had a higher specificity of 92.2%, which is similar to the results shown by Suda et al, 85%, 38 Sigmund et al, 94.7%, 26 and Kasparek et al, 93.3%. 25 Only Gehrke et al reported a specificity of 100%, 21 which has not been replicated by other studies utilizing either the a-defensin laboratory-based immunoassay or lateral flow test.…”
Section: Discussionsupporting
confidence: 90%
“…39 When compared against other biomarkers utilizing the MSIS criteria, the Synovasure lateral flow assay appears to have good sensitivity and high specificity as well. 25,26 Utilizing the ROC curve, the test has an AUC of 0.938, which is similar to synovial WBC, and is only inferior in accuracy as a diagnostic test, to synovial PMN and having at least one positive culture. The Synovasure lateral flow assay measures the levels of a-defensin, which are produced by the synovial PMNs prior to sensitization and conversion to an adaptive immune response.…”
Section: Discussionmentioning
confidence: 99%
“…The alpha defensin lateral flow (ADLF) is a rapid biomarker for test PJI, but the sensitivity and specificity are a controversial idea363738). In a recent study16), the ADLF test was detected PJI with sensitivity and specificity in the criteria of MSIS 84.4% and 96.4%, IDSA 67.3% and 95.5%, and EBJIS 54.4% and 99.3%.…”
Section: Diagnosismentioning
confidence: 99%
“…To assess the performance of alpha defensin lateral flow (ADLF) test for the diagnosis of PJI three classification systems were used [15,16,17,18,19,20]. When the proposed EBJIS criteria were used, the ADLF test performed worse, especially for chronic infections.…”
Section: Discussionmentioning
confidence: 99%